20 años de creación - Moreno, Rodrigo; Grillo Ciocchini, Guillermo; Trapero, Pablo
Negocios (1993): In a car repair shop in the suburbs of Buenos Aires, Rulo and Martin face the daily hazards: money, thieves and romance. They are only vignettes of a routine on daily life. Pablo Trapero has emerged as one of the country’s most influential and important film-makers. His impressive body of work includes long features, "Crane World", "El Bonaerense", "Familia Rodante", "Nacido y criado", "Leonera". Trapero’s early shorts, "Mocoso Malcriado" (1993) and "Negocios" (1995), are insightful observations of life in the sprawling suburbs of Buenos Aires and see him developing his style. [www.nyu.edu]
Keywords: DVD-Video